2021
DOI: 10.1111/ajo.13281
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking third trimester ultrasound measurements and risk of adverse neonatal outcomes in pregnancies complicated by hyperglycaemia: A retrospective study

Abstract: Antenatal ultrasound is used frequently in pregnancies complicated by hyperglycaemia; however, it is unclear which measurements have the greatest association with adverse neonatal outcomes. Aim:To assess the association between third trimester ultrasound parameters with adverse neonatal outcomes in pregnancies complicated by hyperglycaemia.Method: All pregnant women with gestational or type 2 diabetes who birthed in a regional hospital over 12 months were included. A composite adverse neonatal outcome was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Measured fetal abdominal circumference < 90th percentile on 2 ultrasounds at 3- to 4-week intervals has also been shown to provide high reliability in excluding the risk of LGA ( 351 ). Moreover, a recent retrospective study (n = 275) found that estimated fetal weight or abdominal circumference up to the 30th percentile on third trimester ultrasound was associated with a greater risk of adverse neonatal outcomes, comparable to that observed with abdominal circumference or estimated fetal weight > 95th percentile in women with hyperglycemia in pregnancy (including GDM) ( 354 ). These findings suggest the potential utility of fetal biometry at thresholds other than defining SGA or LGA in identifying higher risk pregnancies in GDM.…”
Section: Obstetric Managementmentioning
confidence: 78%
“…Measured fetal abdominal circumference < 90th percentile on 2 ultrasounds at 3- to 4-week intervals has also been shown to provide high reliability in excluding the risk of LGA ( 351 ). Moreover, a recent retrospective study (n = 275) found that estimated fetal weight or abdominal circumference up to the 30th percentile on third trimester ultrasound was associated with a greater risk of adverse neonatal outcomes, comparable to that observed with abdominal circumference or estimated fetal weight > 95th percentile in women with hyperglycemia in pregnancy (including GDM) ( 354 ). These findings suggest the potential utility of fetal biometry at thresholds other than defining SGA or LGA in identifying higher risk pregnancies in GDM.…”
Section: Obstetric Managementmentioning
confidence: 78%
“…Therefore, it is possible that any potential benefit of decreasing growth for a small number of large babies may be more than offset by disadvantages of decreasing growth for the more numerous normal-sized or small babies. Babies below the 25th–30th percentiles may be at greater risk of morbidity than babies up to the 95th–97th percentile70 71 and the risk of stillbirth is lowest between the 75th and 95th birth weight percentiles but stillbirth rates increase as birth weights decrease 72 73. Infant mortality until 1 year of age is lowest in LGA babies, with mortality rates also increasing as birth weights decrease 74.…”
Section: Discussionmentioning
confidence: 99%